Implications of School Dropout for Children’s Future in West Nusa Tenggara Indonesia - I Nyoman Wijana (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to explore, analyse, and describe the implications of children dropping out of school for their future in West Nusa Tenggara Indonesia. The research was conducted in West Lombok Regency using a qualitative method. Interviews, observation, and documentation were conducted to collect the data. Meanwhile, to analyse the data, the researcher used Miles Huberman model of qualitative data analysis. The results of this study indicate that the implications of children who have dropped out of school for their children's future are; inferior in relationships, children become lazy, and less open to develop themselves. It also has implications for families and communities such as; children become unemployed, work odd jobs, create problems in society, and produce new poor families. Given that fact, the implications of dropping out of school for children's future are quite crucial, the local government together with the community have an obligation to solve the problem thoroughly from various perspectives, so that the right formulation can be found to handle it with the appropriate policies.